Consciousness Raising of Sexual Harassment and Gendered Perceptions of Allegations in Social Media among Young Chinese - Jiao, Lin; Wang, Siqi; Song, Jialing (Violence against women, 2025)
This study explored the perceptions of sexual harassment allegations in social media among Chinese university students. The researchers conducted three focus group interviews, asking participants to discuss a high-profile false allegation case. Compared with studies on activists and survivors, the public's perception of the #MeToo movement is understudied, yet examining this aspect is key to its sustainability. We argue digital activism against sexual harassment has raised gender consciousness among young people. However, perceptions of the legitimacy of social media allegations are highly gendered due to the gendered experiences and priorities of men and women, with men having more negative perceptions.